Desain Pembelajaran Bahasa Interaktif dan Inklusif Berbasis Universal Design for Learning (UDL) untuk Guru SMP - Wika Soviana; Mutiarani Mutiarani; Ika Yulianingsih; Aswir Aswir; Farihen Farihen; Yasin Efendi (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to develop an Inclusive Interactive Learning Design for junior secondary school teachers in response to the need for strengthened language education that accommodates learner diversity in Indonesia. Addressing the gap between national inclusive education policies and actual classroom practices, the study employs the Universal Design for Learning (UDL) framework as its theoretical foundation to construct adaptive, interactive, and equitable learning experiences for all students. The research method uses the Research and Development (R&D) method through field studies with data collection in the form of questionnaires, interviews, document observations, and expert validation. The findings indicate that teachers still face limitations in understanding UDL principles, implementing differentiated instruction, and providing interactive learning media, with the highest needs relating to inclusive lesson plan examples, practical modules, and digital learning tools. The study produced a UDL-based interactive learning design, inclusive lesson plans, differentiated worksheets, and digital media prototypes, all of which were rated highly feasible by expert validators (91%). The study concludes that structured, technology-supported interactive–inclusive learning designs have strong potential to enhance the implementation of equitable and participatory language education for diverse learners in Indonesian junior secondary schools.